Model test study of the mechanical characteristics of the lining structure for an urban deep drainage shield tunnel - Guo, Rui; Zhang, Maoyi; Xie, Hongming; He, Chuan; Fang, Yong; Wang, Shimin (Tunnelling and underground space technology, 2019)
In this paper, we conducted a series of model tests aimed at studying mechanical behavior of a shield tunnel structure under the combined action of external soil-water load and internal water pressure. The results show that the single segmental lining is in the state of large eccentric compression-bending or tension-bending for lower internal water pressure. However, because the secondary lining of the double lining shares the structural tension, the segmental lining is still undergoing compression-bending even during high internal water pressure. The double lining is better than the single segmental lining from the standpoints of the structure’s bearing capacity and waterproof performance. The internal water pressure has almost no effect on the structural bending moments, while it has a significant impact on the structural axial force. As the internal water pressure increasing, the compression of the segment gradually decreases and even changes to tension, and the tension of the secondary lining increases rapidly. Basically, under the high internal water pressure, structure fractures appears first at the hance of the secondary lining, then appears at the vault and the arch bottom. Finally the corresponding outside segments are broken down. The thickness of the secondary lining should be determined from the aspect of matching the stiffness of the segment, and ensure that the structure will not undergo tensile failure when subjected to the high internal water pressure.